Defeasible Reasoning in Islamic Legal Theory - Komath, Muhammed (Informal Logic, 2024)
Logicians commonly understand nonmonotonic types of reasoning can warrant rational acceptance of conclusions. The significance and legitimacy of these forms of arguments, which were long considered fallacious, has been contentious among logicians in the Aristotelian logical tradition. In contrast, Islamic jurisprudence (fiqh), has long recognised the importance of non-deductive forms of reasoning, and demonstrated how conventionally understood fallacies are not essentially fallacies. Qiyās – generally representing analogical reasoning – is such a case of defeasible reasoning in Islamic legal theories. I show through works of two emblematic medieval Muslim jurist-logicians, al-Juwainī and al-Ghazzālī, that understanding the legitimacy of non-deductive forms of arguments is core to Islamic legal theories (usūl al-fiqh), which proposed a dialectical method (jadal) of approach.